Students' ICT conceptions and the challenges in acquiring ICT skills for engineering learning - Ali, Rosmah (2013)
Graduates in today's digital world are expected to possess a certain level of command in ICT skills. These skills are particularly important for those in the technical and engineering disciplines. As an effort to gain insight into students' conceptions and the challenges in acquiring ICT skills, one-on-one and focus group interviews were conducted on diploma-level engineering students. Interview transcriptions were analyzed to produce themes on students' conceptions of ICT skills and the challenges faced in inculcating ICT skills. This study found that students' conception of ICT skills were mainly as informative, constructive, communicative or situative tools. Some of the challenges students faced in acquiring ICT skills were related to internet connectivity, lack of software and hardware resources, and lack of practical skills.